No association of cigarette smoking and depressive symptoms with cortisol concentration in adolescents. Results from a population-based Swedish cohort. (July 2021) - Raffetti, Elena; Andersson, Filip; Donato, Francesco; Kong, Linghua; Efstathopoulos, Paschalis; Lavebratt, Catharina; Forsell, Yvonne; Galanti, Maria Rosaria
Highlights: Current smoking was not related to salivary cortisol concentration in adolescents. Salivary cortisol concentration was not associated with depressive symptom scales. No evidence of a role of HPA axis in smoking-depressive symptoms association. Abstract: Several studies have shown that smoking increases the risk of depressive symptoms, and suggested a possible role of the hypothalamic-pituitary-adrenal axis in the smoking-depression pathway. This study aimed to assess if smokers have higher cortisol levels than non-smokers, and if higher cortisol levels are associated with depressive symptoms. Saliva samples were collected from a subgroup of 409 participants at enrolment (13-14 years old) and two years later (15-16 years old). First, we examined the association between smoking phenotypes and cortisol concentration. Second, we evaluated whether these associations differed between adolescents with and without depressive symptoms. The mean difference between smokers and non-smokers in cortisol concentrations was close to zero at both time points. For instance, the adjusted mean difference for morning cortisol concentration between current and non-current smokers was 0.000 µg/dl [95% CI -0.055, 0.056]. In addition, there were no differences in cortisol concentration at the second time-point between those who had smoked and those who did not during the two previous years. Moreover, cortisol levels were not associated with depressive symptoms. The hypothesis that dysregulation of the hypothalamic-pituitary-adrenal axis might be involved in the association between smoking behavior and depressive symptoms during adolescence was not supported by this data.